Images of gender among Western and Eastern perspective the case of Bahrain - Brilanda Bushati; Adriana Galvani (European Journal of Geography)
The theme of gender is largely discussed in private and public arenas, since it concerns questions connected to the concept of sustainability. It involves political arguments and requests economic solutions, not only humanistic notions. It is also a complex argument to study, with many faces and perspectives, connected to religions and social-economic development of different areas. Today two main visions are facing each other, depending on South-North/Western and Eastern societies. Governmental and Inter-governmental organizations are launching programs and laws in order to gain equality and parity between both sexes in every condition of life, since assuring human rights is a pre-requisite of human development and development in general. In addition, achieving gender equality and empowering all women and girls is essential for achieving sustainable development, one of the post- 2015 sustainable development goals.